Change in the Quality of Scar Following Release of Contracture – A Study of 50 Cases (Journal of Surgical Sciences, 2026)
Background: Thick tender scars are commonly associated with contractures. There is a difference of opinion on how they should be addressed. The study was designed to find out how the scars respond to release of tension.Methods: 50 cases with thick contracted scars were treated by release of contractures. Thickness and tenderness of the scars were measured pre-operatively, 2 weeks after surgery and 6 weeks after surgery to record the changes of the scar.Results: The scars demonstrated significant reduction in thickness and tenderness within 6 weeks of surgery.Journal of Surgical Sciences 2023;27(1): 3-10